The Behaviour of Laboratory Soil Electrical Resistivity Value under Basic Soil Properties Influences. (30th January 2015) - Hazreek, Z A M; Aziman, M; Azhar, A T S; Chitral, W D; Fauziah, A; Rosli, S
Abstract: Electrical resistivity method (ERM) was a popular indirect geophysical tools adopted in engineering, environmental and archaeological studies. In the past, results of the electrical resistivity value (ERV) were always subjected to a long discussion and debate among the related parties such as an engineers, geophysicists and geologists due to its lack of clarification and evidences in quantitative point of view. Most of the results produced in the past was always been justified using qualitative ways which difficult to be accept by certain parties. In order to reduce the knowledge gap between those parties, this study has performed a laboratory experiment of soil box resistivity test which supported by an additional basic geotechnical test as referred to particle size distribution test (d), moisture content test ( w ), density test (ρbulk ) and Atterberg limit test (LL, PL and PI). The test was performed to establish a series of electrical resistivity value with different quantity of water content for Clayey SILT and Silty SAND soil. It was found that the ERV of Silty SAND (600 - 7300 Ωm) was higher than Clayey SILT (13 - 7700 Ωm) due to the different quantity of basic soil properties value obtained from the basic geotechnical test. This study was successfully demonstrated that the fluctuation of ERV has greatly influenced by the variations of the soil physical properties (d, w, ρbulk, LL, PL and PI). Hence, the confidence level of ERV interpretation will be increasingly meaningful since it able to be proved by others parameter generated by laboratory direct test.